Dietary patterns and diabetes mellitus risk in Indonesian adolescents: A literature review - Aulia Diva Azzahra; Hayu Iyaka Nastaina (AcTion: Aceh Nutrition Journal, 2026)
Adolescents in Indonesia increasingly consume high-sugar, saturated fat, and ultra-processed foods, contributing to a rising risk of type 2 Diabetes Mellitus (DM). Low attention to healthy eating and poor awareness of its impact remain major gaps in the literature. This systematic review aimed to determine the association between dietary patterns and DM risk among adolescents and promote early prevention. A systematic review was conducted using Google Scholar, PubMed, ScienceDirect, and ProQuest with the following inclusion criteria: discussing the influence of diet on DM among Indonesian adolescents, written in English or Indonesian, published between 2020-2025, full-text and open access, and excluding reviews, theses, dissertations, or proceedings. Selection followed the PRISMA method, yielding six studies for analysis. The results showed that adolescents consuming sugary drinks >3 times/week had a 2.91 higher risk of abnormal blood glucose, while similar soft drink intake increased the risk of obesity (OR = 8.53), which is directly linked to type 2 DM. Most adolescents also failed to meet the daily fruit and vegetable intake recommendations. In conclusion, adolescent diets are high in sugar and low in fiber, worsened by poor nutritional literacy. School-and family based interventions, restriction of sugary drink availability, and promotion of fruit and vegetable consumption are recommended for early DM prevention.